Patient Privacy Protection in the Use of Social Media as a Tool for Doctor Consultation from a Legal Perspective - Harri Romadhona; Ifan Sadewa; Karomah Alif Sabilla Rustam Sutoto; Ridwan Ridwan (Siber Nusantara of Law and Politic Review, 2024)
In this digital age, interactions between patients and doctors are increasingly moving to social media platforms, which can have a significant impact on the accessibility and affordability of healthcare services. However, it is important to note that when medical consultations take place online, new legal challenges arise in terms of information confidentiality, professional responsibility, and patient protection. This journal addresses the issue of legal protection for patients who communicate with doctors via social media. This study examines the legal framework governing online medical consultations, including patient privacy rights, doctors' professional ethics, and legal accountability. The emphasis is on identifying potential legal gaps and developing solutions to improve legal protection for patients in this context. This journal's approach aims to contribute to the development of appropriate and convincing regulations to address legal issues that arise as communication technology advances.